Joseph Ratzinger’s Argument for the Epistemological Seriousness of Faith - Kaucha, Krzysztof Cezary (Verbum vitae, 2021)
Christianity, and the Christian faith, seems to be losing when confronted with scientific reason and scientific certainty. Christianity needs new arguments for the epistemological seriousness of its faith. Those could be found in Joseph Ratzinger’s writings, providing new insights into fundamental theology. The subject of faith as an element that is crucial to him (and to Christianity) pervades all his works. This paper aims at proving that Ratzinger has worked out an original epistemological way of defending the Christian faith. It is an attempt to recreate his argument on the basis of his entire intellectual output. The present research leads to the conclusion that Ratzinger’s way of argumentation is quite unique. In classical fundamental theology, the Christian faith (comprehended mostly as an individual act of faith) is placed at its end point, while in Ratzinger’s fundamental theology, faith (understood mostly as a historical and communal act) is practically a point of departure. From the beginning of his reasoning Ratzinger (due to his meta-faith perspective) persuades that the Christian faith is epistemologically very serious. Faith may not only manifest its presence alongside other serious attitudes to reality, but also be capable of demonstrating its foundation, rationality, originality, uniqueness, and even absoluteness (definitiveness).